Evaluation of One Egg per Day on Iron and Anemia Status Among Young Malawian Children: A Randomized Controlled Trial. (7th June 2021) - Werner, Rochelle; Arnold, Charles; Caswell, Bess; Iannotti, Lora; Lutter, Chessa; Maleta, Kenneth; Stewart, Christine
Abstract: Objectives: Young children with complementary feeding diets that lack diversity and have low micronutrient density are at risk of iron deficiency anemia. Our objectives were to determine the impact of supplementing diets with 1 egg/day on: (1) plasma ferritin, soluble transferrin receptor (sTfR), and hemoglobin (Hb) concentrations; and (2) the prevalence of iron deficiency (ID), anemia, and iron deficiency anemia (IDA). Methods: Children age 6–9mo in the Mangochi District of Malawi were individually randomized to receive 1 egg/day for 6mo (n = 331) or continue their usual diet (n = 329). Venous blood samples were collected at enrollment and a 6mo follow-up by assessors masked to group assignment. Plasma ferritin, sTfR, c-reactive protein (CRP), and α1-acid glycoprotein (AGP) were assessed using ELISA and hemoglobin was measured using Hemocue analyzers. Ferritin and sTfR were corrected for inflammation using CRP and AGP in linear regression models. Ferritin, sTfR, and hemoglobin concentrations were compared between groups using linear regression models, adjusting for baseline values. The prevalence ratios (PR) of ID (fer < 12μg/L, sTfR >8.3mg/L, or total body iron< 0mg/kg), anemia (Hb< 11g/dL), and IDA (Hb < 11g/dL and ID) were compared between egg and control groups using binomial or Poisson regression models. Results: A total of 585 children were included in this analysis (Egg: n = 286; Control: n = 299). At enrollment, the prevalence of anemia and IDA was 61% and 55%. At the 6mo follow-up, there was no difference between groups in inflammation-adjusted ferritin (geometric mean [95% CI]; Egg: 6.52µg/L [5.98, 7.10]; Control: 6.82 [6.27, 7.42]) or sTfR (Egg: 11.34mg/L [10.92, 11.78]; Control: 11.46 [11.04, 11.89]) concentrations. There was also no difference in mean hemoglobin concentration between groups (mean [95%CI]; Egg: 11.0g/L [10.8, 11.1]; Control:11.1 [11.0, 11.3]). Overall, 43% of children had anemia, 89% had ID, and 40% had IDA. No group-level differences were observed in the prevalence of anemia [PR: 1.15 (95% CI: 0.96, 1.38)], ID [PR: 0.99 (0.94, 1.05)], or IDA [PR: 1.12 (0.92, 1.36)]. Conclusions: Iron and anemia indices did not differ between the egg intervention group and control group. Other interventions are needed to address the high prevalence of iron deficiency and anemia among young, Malawian children. Funding Sources: Bill & Melinda Gates Foundation.